Interplay between systemic inflammation, anemia, and mycobacterial dissemination and its impact on mortality in TB-associated HIV: a prospective cohort study - Araújo-Pereira, Mariana; Schutz, Charlotte; Barreto-Duarte, Beatriz; Barr, David; Villalva-Serra, Klauss; Vinhaes, Caian L.; Ward, Amy; Meintjes, Graeme; Andrade, Bruno B. (Frontiers in Immunology, 2023)
Introduction Anemia frequently affects people living with HIV (PLHIV). Nevertheless, the impact of anemia on treatment outcomes of patients with HIV-associated tuberculosis (TB) and the underlying molecular profiles are not fully characterized. The aim of this study was to investigate the interplay between anemia, the systemic inflammatory profile, dissemination of TB and death in HIV-TB patients in an ad hoc analysis of results from a prospective cohort study. Methods 496 hospitalized PLHIV ≥18 years old, with CD4 count <350 cells/μL and high clinical suspicion of new TB infection were enrolled in Cape Town between 2014-2016. Patients were classified according to anemia severity in non-anemic, mild, moderate, or severe anemia. Clinical, microbiologic, and immunologic data were collected at baseline. Hierarchical cluster analysis, degree of inflammatory perturbation, survival curves and C-statistics analyses were performed. Results Through the analysis of several clinical and laboratory parameters, we observed that those with severe anemia exhibited greater systemic inflammation, characterized by high concentrations of IL-8, IL-1RA and IL-6. Furthermore, severe anemia was associated with a higher Mtb dissemination score and a higher risk of death, particularly within 7 days of admission. Most of the patients who died had severe anemia and had a more pronounced systemic inflammatory profile. Discussion Therefore, the results presented here reveal that severe anemia is associated with greater TB dissemination and increased risk of death in PLHIV. Early identification of such patients through measurement of Hb levels may drive closer monitoring to reduce mortality. Future investigations are warranted to test whether early interventions impact survival of this vulnerable population.